Hybrid learning spaces. Towards an education of the future at the Guayaquil University - César Gerardo Mejía Gallegos; David Enmanuel Michalón Dueñas; Raúl Andrés Michalón Acosta; Raúl López Fernández; Diana Eliza Palmero Urquiza; Samuel Sánchez Gálvez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2017)
The pedagogical hybrid learning model is increasingly used in higher education, due to the fact that it promotes significant changes in learning. The objective of this article is to facilitate a theoretical proposal on the inverted class methodology, for its implementation in the teaching process of the Dentistry Experimental Faculty of the Guayaquil University. This concept implies opening effective opportunities for dialogue and collaborative content construction, as well as the promotion of digital culture in terms of collaboration and cooperation between managers and teachers to act differently in the classroom.